The Effect of Papaya Juice Consumption on Hemoglobin Levels of Pregnant Women at Depok Jaya Public Health Center - alfiah rahmawati; Dian Reflisiani (PROFESSIONAL HEALTH JOURNAL, 2025)
Introduction: Anemia during pregnancy remains a significant public health concern, particularly in low-resource settings where nutritional deficiencies are common. Iron supplementation is a standard intervention; however, its effectiveness may be enhanced by nutrient-rich foods that improve iron absorption. Papaya is a local fruit high in vitamin C and folate, essential for hemoglobin synthesis. Objectives: This study aimed to determine the effect of papaya juice supplementation alongside iron tablets on the hemoglobin levels of pregnant women. Methods: A quasi-experimental study with a pre-test and post-test control group design was conducted among pregnant women in the Depok Jaya Health Center area. Thirty-six participants were selected using purposive sampling and divided equally into control and intervention groups. The control group received only iron tablets, while the intervention group consumed papaya juice daily in addition to iron tablets for 14 days. Hemoglobin levels were measured before and after the intervention, and data were analyzed using paired and independent sample t-tests. Results: The mean hemoglobin level in the intervention group increased substantially after 14 days, while the control group showed a more minor increase. Statistical analysis indicated significant improvements within both groups and a significant difference between the intervention and control groups (p-value <0.05; α<0.05). Conclusions: Papaya juice supplementation enhanced the effectiveness of iron tablets in improving hemoglobin levels among pregnant women. As an affordable and locally available food, papaya has the potential to be integrated into maternal nutrition programs to reduce anemia in pregnancy. Further research is recommended to confirm long-term benefits.